ECOSOPHY OF SYAIR IKAN TERUBUK - Mohd. Fauzi; Tengku Silvana Sinar; Dwi Widayati; Bahagia Tarigan (Universitas Muhammadiyah Semarang, 2021)
This study is intended to analyze the Ecosophy of Syair Ikan Terubuk using a critical ecolinguistic approach. This type of research is descriptive qualitative. In collecting data, researchers used the documentation method. The data of this research are lexicons, phrases, and verses containing the ecosophy of environmental preservation, especially the aquatic environment, which is sourced from Syair Ikan Terubuk. The results showed that the lingual units in Syair Ikan Terubuk has positive values and encourage people to love, care for and preserve their environment (ecosophy values). This Syair Ikan Terubuk presents 60 types of fish in the Bengkalis sea and in Puyu-Puyu Lake with their respective characters. Although this poem is a symbolic poem about human behavior, but it has a very strong connection with the environment. It is proven that in the past a large number of fish mentioned in the previous poem existed and became a source of sustenance for the Bengkalis community, but nowadays it is very difficult to find them, even most of them are no longer found. At least by analyzing these verses, the current generation and so on will not make matters worse. The ecosophy values of the Malay ancestors in caring for and living side by side with their natural surroundings are clearly stated in this Syair Ikan Terubuk.